2022
DOI: 10.1002/iub.2696
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic initiation factor 6 repression mitigates atherosclerosis progression by inhibiting macrophages expressing Fasn

Abstract: Atherosclerosis, a chronic inflammatory disease that often leads to myocardial infarction and stroke, is mainly caused by lipid accumulation. Eukaryotic initiation factor 6 (Eif6) is a rate‐limiting factor in protein translation of transcription factors necessary for lipogenesis. To determine whether Eif6 affects atherosclerosis, Eif6+/− mice were crossed into Apoe−/− background. Apoe−/−/Eif6+/− mice on high fat diet showed significant reduction in atherosclerotic lesions and necrotic core content in aortic ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, it can be concluded that the m.15059G>A mutation may be associated with a change in the intracellular synthesis of fatty acids, despite the fact that the intracellular cholesterol content was not modified. Numerous studies suggest a strong correlation between fatty acid synthesis and the development of atherosclerosis 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that the m.15059G>A mutation may be associated with a change in the intracellular synthesis of fatty acids, despite the fact that the intracellular cholesterol content was not modified. Numerous studies suggest a strong correlation between fatty acid synthesis and the development of atherosclerosis 33,34 .…”
Section: Discussionmentioning
confidence: 99%